Incidence of Misplaced Pedicle Screw in Free Hand Technique in Spine Fixation Patients - Sahibzada Haseeb Ahmed, Yasir Mehmood, Sajid Uthmanzai, Muhammad Shoaib, M.Arsalan Azmat Swati, M Kashif, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the frequency of pedicle screw displacement during free-hand technique in spinal fixing Material & Methods: This retrospective prospective study was carried out at Department of Neurosurgery Lady Reading Hospital Peshawar from June 2021 to December 2021. Total 90 patients were included. The screws were implanted utilising a free-hand placement technique. Facet joints and transverse processes were among the anatomical landmarks that were revealed. According to the level approached, the pedicle screw's entry location was selected. The insertion was done medially to the intersection of the origin of the transverse process and the lamina in the proximal thoracic spine and laterally to the pars interarticularis (T1 to T3). Results: 90 people in all were included in the trial. With a mean age of 37.5 years, the age varied from 15 to 60 years. Male to female ratio was 2:1, with 60 (66.7%) males and 30 (33.3%) females. Pedicle screws totaling 540 were inserted. 310 (57.4%) of the screws were placed at the lumbar spine, followed by 198 (36.7%) at the thoracic spine and 32 (5.9%) at the sacral spine. Conclusion: Pedicle screw cortical violation was found to be very high. Small pedicle breaches, however, have the potential to cause neurological lesions that can be reversed if the misaligned screws are fixed. Keywords: Freehand technique, Pedicle screw fixation, Spinal fracture